Peran Dinas Pariwisata dan Kebudayaan Kota Pariaman dalam Melestarikan Tradisi Hoyak Tabuik di Kota Pariaman - Whindy Hijratul Khaira; Syamsir Syamsir (YASIN, 2026)
The Hoyak Tabuik tradition is a cultural heritage of the people of Pariaman City that has historical, social, religious, and cultural values, while also serving as one of the region’s leading cultural tourism attractions. However, changing times, budget constraints, and low youth involvement have become challenges in preservation efforts. This study aimed to analyze the role of the Tourism and Culture Office of Pariaman City in preserving the Hoyak Tabuik tradition and to identify inhibiting and supporting factors in its implementation. This study used a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation involving informants consisting of the Head of the Culture and Creative Economy Division, Junior Expert Cultural Officer, Tabuik organizing committee, tuo Tabuik, and the community of Pariaman City. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that the Tourism and Culture Office of Pariaman City had carried out its roles as a regulator, dynamizer, facilitator, and catalyst in preserving the Hoyak Tabuik tradition. These roles were realized through the formulation of technical policies, coordination among institutions and the community, provision of budgets and supporting facilities, and cultural promotion through social media and digital media. The inhibiting factors in preservation included budget constraints, the absence of a specific Regional Regulation, differences in community perspectives, and the lack of youth involvement. Meanwhile, the supporting factors included local government support, the involvement of tuo Tabuik and the community, high tourist enthusiasm, and the strong cultural values of the people of Pariaman City. Thus, this study affirms that the preservation of the Hoyak Tabuik tradition requires strengthened regulation, budgetary support, institutional coordination, digital cultural promotion, and active youth participation so that the sustainability of local cultural heritage can be maintained more effectively.